The Effectiveness Of Using Pre-Questioning On The Reading Comprehension Achievement For The Seventh Grade Students Of MTs Negeri Plupuh Sragen In 2011/2012 Academic Year - Aulia , Muhammad Fakhrial (2012)
This research aims to describe the effectiveness of using pre-questioning on the reading comprehension achievement for the seventh grade students of of MTs Negeri Plupuh Sragen in 2011/2012 academic year. This research is a qualitative research. This writer uses descriptive method to present the data. The data of this research are lesson plan, interview scripts, and test results. The data sources are event, informants, and documents. The results of this research show that, firstly, the implementation of pre-questioning on the reading comprehension achievement is helpful for the students. The students who use pre-questioning on reading achievement are better than students who do not use the pre-questioning on reading achievement. Secondly, the effectiveness in using pre-questioning on reading comprehension achievement is effective. The third, problems faced by the students in using pre-questioning on the reading comprehension achievement are: the students are lack in mastery vocabulary, the students can make wrong understanding in translating the sentence of the reading comprehension, students are hard to read the meaning of reading comprehension content and the students only read the questions first